fate of modernism - Lidin, Konstantin (project baikal, 2021)
It has long been recognized that children take more after their grandparents than after their parents. This phenomenon of “generation-skipping” succession is so widely observed that it cannot be accidental. Today’s trends in the development of architecture have much in common with the predecessor of postmodernism (although it seems to be a thing in the past) rather than postmodernism itself. A careful study may unveil the patterns and ideas of modernism in today’s iconic structures. The examples are around us. The 130 Quarter is probably the only one new project comparable in its scale to the urban planning ideas of the Irkutsk sixtiers: the Baikal Beam, the Green Diameter and the Cultural Center. Despite its external differences, it is a successor in the continuous chain of the development of architecture.
Keywords: modernism; Green Diameter; Cultural Center